Conceitos atuais na endocrinologia para os clínicos e estudantes de Medicina Tireoidite de Hashimoto: disfunção tireoidiana clínica e subclínica - Travassos Neto, Paulo (Revista Científica da Faculdade de Medicina de Campos, 2018)
Hashimoto’s thyroiditis (HT) is an autoimmune and inflammatory disease in which antibodies are directed against the thyroid gland leading to chronic inflammation and hypothyroidism. The autoimmunity against thyroid antigens can be associated to genetic background and environmental factors. Thyroid peroxidase (TPO) and thyroglobulin (TG) are the major autoantigens for characterizing the disease. And the pathogenic mechanism is related to the activation of autoreactive CD4+ T cells, CD8+ cytotoxic T cells and antithyroid antibody producing-B cells. The treatment for hypothyroidism is based on thyroid hormone replacement, the levothyroxine. This review briefly discusses the clinical and pathogenic profile of HT and the importance of a correct diagnostics.